Serine Metabolism Regulates YAP Activity Through USP7 in Colon Cancer - Zhao, Xiaoya; Fu, Jianfei; Hu, Bin; Chen, Lin; Wang, Jing; Fang, Jinyong; Ge, Chenyang; Lin, Haiping; Pan, Kailing; Fu, Liang; Wang, Lude; Du, Jinlin; et al. (Frontiers in Cell and Developmental Biology, 2021)
Metabolic reprogramming is a vital factor in the development of many types of cancer, including colon cancer. Serine metabolic reprogramming is a major feature of tumor metabolism. Yes-associated protein (YAP) participates in organ size control and tumorigenesis. However, the relationship between YAP and serine metabolism in colon cancer is unclear. In this study, RNA sequencing and metabolomics analyses indicated significant enrichment of the glycine, serine, and threonine metabolism pathways in serine starvation–resistant cells. Short-term serine deficiency inhibited YAP activation, whereas a prolonged response dephosphorylated YAP and promoted its activity. Mechanistically, USP7 increases YAP stability under increased serine conditions by regulating deubiquitination. Verteporfin (VP) effectively inhibited the proliferation of colon cancer cells and organoids and could even modulate serine metabolism by inhibiting USP7 expression. Clinically, YAP was significantly activated in colon tumor tissues and positively correlated with the expression of phosphoglycerate dehydrogenase (PHGDH) and USP7. Generally, our study uncovered the mechanism by which serine metabolism regulates YAP via USP7 and identified the crucial role of YAP in the regulation of cell proliferation and tumor growth; thus, VP may be a new treatment for colon cancer.